Formulation of Papaya Leaf (Carica papaya L.) Decoction Extract Spray as a Botanical Insecticide against House Flies (Musca domestica) - Agustin, Kiki Arianti; Surahmaida, Surahmaida; Yuliarni, Floreta Fiska (Jurnal Biologi Tropis, 2026)
The housefly (Musca domestica) is a mechanical vector for various infectious diseases, the control of which is still dominated by synthetic pesticides. This study aims to formulate and test the efficacy of a spray preparation of papaya (Carica papaya L.) leaf aqueous extract with variations in concentration (F1: 20%, F2: 40%, and F3: 60%) against housefly mortality. The experimental design used three replications for each treatment, utilizing a total of 120 houseflies, with 10 flies placed in each test container. A negative control group was included to ensure validity. Observations were conducted every 10 minutes over a 1-hour exposure period, and the collected data were analyzed descriptively. The results showed that an increase in extract concentration was directly proportional to the speed and rate of fly mortality. The negative control showed no mortality (0.00%). The F1 formulation resulted in an average mortality of 43.33%, while F2 and F3 demonstrated very high efficacy at 86.66% and 90.00%, respectively. Based on the killing speed, F3 recorded the highest cumulative mortality within the first 10 minutes (17 flies) compared to F2 (8 flies) and F1 (2 flies). The 40% (F2) and 60% (F3) concentration papaya leaf extract spray preparations possess potential and environmentally friendly insecticidal activity.